2010
DOI: 10.1148/rg.303095049
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging of Scrotal Tumors and Pseudotumors

Abstract: Magnetic resonance (MR) imaging is an important imaging technique in the evaluation of scrotal masses, providing a useful adjunct to ultrasonography (US). Although US is the modality of choice for initial evaluation of scrotal pathologic conditions because of its wide availability, low cost, and high sensitivity for detection of testicular and paratesticular disease processes, US findings may occasionally be inconclusive. MR imaging may provide additional information in these cases, often affecting patient man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
200
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(214 citation statements)
references
References 34 publications
3
200
0
7
Order By: Relevance
“…However, a confident preoperative characterization of various benign intratesticular entities, including dilatation of rete testis, orchitis, epidermoid cyst, infarction, fibrosis and hematoma, for which radical orchiectomy is unnecessary is important. [3][4][5][6][7][8] In these patients, a more conservative approach, as follow-up, tumor enucleation or testissparing surgery may be justified. Sonography, although the primary imaging technique for the evaluation of scrotal pathology, 1,2 because of its wide availability, low cost and high sensitivity in the identification of scrotal lesions, does not always allow a confident preoperative characterization of scrotal masses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, a confident preoperative characterization of various benign intratesticular entities, including dilatation of rete testis, orchitis, epidermoid cyst, infarction, fibrosis and hematoma, for which radical orchiectomy is unnecessary is important. [3][4][5][6][7][8] In these patients, a more conservative approach, as follow-up, tumor enucleation or testissparing surgery may be justified. Sonography, although the primary imaging technique for the evaluation of scrotal pathology, 1,2 because of its wide availability, low cost and high sensitivity in the identification of scrotal lesions, does not always allow a confident preoperative characterization of scrotal masses.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] The technique due to its wide field of view, multiplanar capabilities, high contrast and spatial resolution has proved satisfactory in the localization of a scrotal mass, in the differentiation of paratesticular masses with respect to tumor morphology and tissue characteristics, in the distinction between benign from malignant intratesticular lesions and in the evaluation of the local extent of the disease in cases of testicular carcinomas. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The technique is mainly recommended when sonographic findings are inconclusive or inconsistent with clinical findings. 5,6 In accordance with previous reports, this study demonstrated high accuracy of conventional MR sequences in characterizing both paratesticular and intratesticular mass lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of particulate matter within the lesion produces hyper-reflective spots or the characteristic comet tail image in the presence of gas. Color Doppler US reveals peripheral hyperemia and CEUS shows an intense marginal absorption of contrast agent in the capillaries of the granulation tissue [13].…”
Section: Testicular Abscessmentioning
confidence: 99%